Neurologic Assessment and Management of the Multiple Ligament Injured Knee: A Review and Synthesis of Current Evidence - Hoit, Graeme; Farag, Jordan; Whelan, Daniel B. (The Journal of Knee Surgery, 2020)
Knee dislocations are rare but devastating injuries that can often be associated with concomitant nerve injury, most often of the common peroneal nerve. Prompt diagnosis, investigation, and appropriate treatment are important in this subset of patients. This article provides an overview of relevant injury demographics, anatomy, diagnosis, and prognosis, and suggests a treatment algorithm for nerve injury associated with multiligament knee injury.
Keywords: knee dislocation; multiligamentous; peroneal nerve; neuropathy